1997
DOI: 10.1152/ajpregu.1997.273.1.r259
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for changes in vasopressin during acute exposure at 3 atm abs air

Abstract: Plasma arginine vasopressin (AVP) concentration is reduced in human subjects during prolonged saturation dive exposures of 4 atmospheres absolute (atm abs) and greater. The objectives of the present study were to determine if AVP would be reduced in eight male subjects during a 1-h exposure of 3 atm abs air and, if so, to determine the mechanisms responsible for the AVP response. Assessments of transmural central venous pressure (central venous pressure-esophageal pressure) and cardiac volume measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In opposite, water immersion is followed by AVP suppression by mechanisms that are incompletely defined, but it appears that not only cardiopulmonary mechanoreceptors but also arterial baroreceptors mediate the response ( 86 ). It was shown that the exposure of 3 atm air (that corresponds to the dive of 20 m depth) for 1 hour leads to a significant reduction of plasma osmolality and the reduction in AVP plasma level ( 87 ). Thus, the AVP release during the dive is a result of combined actions of stimulating and inhibitory factors.…”
Section: Discussionmentioning
confidence: 99%
“…In opposite, water immersion is followed by AVP suppression by mechanisms that are incompletely defined, but it appears that not only cardiopulmonary mechanoreceptors but also arterial baroreceptors mediate the response ( 86 ). It was shown that the exposure of 3 atm air (that corresponds to the dive of 20 m depth) for 1 hour leads to a significant reduction of plasma osmolality and the reduction in AVP plasma level ( 87 ). Thus, the AVP release during the dive is a result of combined actions of stimulating and inhibitory factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a hyperbaric environment, both pressure and gas density are elevated. Torii et al (32) reported that a threefold increase in normal gas density at 3 atm abs (from 1.2 kg/m 3 at 1 atm abs to 3.5 kg/m 3 at 3 atm abs) caused increased resistance in the respiratory tract, resulting in increasing negativity of the inspiratory intrathoracic pressure (Pes). This increased negative Pes could lead to an increased venous return and hence to an increased central venous pressure (CVP).…”
Section: Discussionmentioning
confidence: 99%